GE_GERICHTE P/18800/2014 vom 8. Mai 2018 - GE Cour de justice (2018)
LÉSION CORPORELLE PAR NÉGLIGENCE ; DISPOSITIONS PÉNALES DE LA LCR ; RUPTURE DU LIEN DE CAUSALITÉ ; TORT MORAL | CP.125.al1; CP.125.al2; CP.12.al3; CP.47; CP.34.leta; LCR.90; LCR.31.al1; LCR.36.al4; LCR.58; LCR.59; CO.47; CO.44.al1; CPP.9; CPP.325.al1